Affirmative Sexual Consent in Canadian Law, Jurisprudence, and Legal Theory - Vandevort, Lucinda (Columbia Journal of Gender and Law, 2012)
This article examines the development of affirmative sexual consent in Canadian jurisprudence and legal theory and its adoption in Canadian law. Affirmative sexual consent requirements were explicitly proposed in Canadian legal literature in 1986, codified in the 1992 Criminal Code amendments, and recognized as an essential element of the common law and statutory definitions of sexual consent by the Supreme Court of Canada in a series of cases decided since 1994. Although sexual violence and non-enforcement of sexual assault laws are worldwide phenomena, the international scholarly literature reflects limited awareness of these developments in Canadian law. This article remedies that gap in the literature. The Canadian experience with the definition of sexual consent as communicated “voluntary agreement” demonstrates the value of this conceptualization of consent; the definition provides a well-defined set of nondiscretionary reference points for legal analysis of the facts in sexual assault offenses. The effect is to facilitate effective enforcement of the sexual assault laws and affirm the right to sexual autonomy, sexual self-determination, and equality, consistent with fundamental principles of individual human rights. For all these reasons, familiarity with the Canadian experience may be useful to those engaged with the reform of rape and sexual assault laws in other jurisdictions.